Penerapan Latent Class Regression Analysis dalam Segmentasi Pasar - Musmirani, Musmirani; Purnamasari, Ika; Suyitno, Suyitno (EKSPONENSIAL, 2020)
Cluster analysis is a method of grouping observation objects into several classes. One method of mixed-scale data grouping is Latent Class Regression Analysis (LCRA). The purpose of this research is to classify the opinion of Wardah's product consumers on marketing strategies (product aspects, price aspects, location aspects, and promotion aspects) PT. Paragon Technology and Innovation Regional Samarinda in 2017 with covariate variables arelength of subscription, type of work and age of consumers. Estimation of LCRA using the Expectation Maximization (EM) method, solved by the Newton-Raphson method. The result of LCRA analysis that based on consumer opinion on market segmentation, consumers are grouped into two classes.The first class is 31 consumers that strongly agrees the aspects of product, price, promotion and position are appropriate market segmentation, and the second class is 69 that quite agrees product aspects, prices, promotion and position is the appropriate market segmentation.